2021
DOI: 10.1590/0102-311x00174619
|View full text |Cite
|
Sign up to set email alerts
|

Judicialização no acesso a medicamentos: análise das demandas judiciais no Estado do Rio Grande do Norte, Brasil

Abstract: Este trabalho objetivou analisar os processos judiciais que solicitavam medicamentos ao Estado do Rio Grande do Norte, Brasil, no período de 2013 a 2017, descrevendo suas características sociodemográficas, jurídicas e médico-sanitárias. Trata-se de um estudo descritivo, cuja unidade de análise foi o processo judicial individual de solicitação de medicamentos, em que o estado é réu. Os dados foram obtidos por meio de consulta ao sítio eletrônico do Tribunal de Justiça do Estado do Rio Grande do Norte. Foram ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 23 publications
0
5
0
12
Order By: Relevance
“…With an understanding that this was a convenience sample, it was not possible to address any trends that may have increased or reduced the impacts of these lawsuits on the state's health management, although it was possible to describe the characteristics and behavior of expenditure on medications and the relevance of antineoplastic drugs in a Northeastern Brazilian state that ranks as one of the richest (GDP) in the region. The following comparisons with other ndings in the literature have limitations, since the studies present different methodologies for collecting and describing the pro le characteristics of judicialization, as recently cited by Oliveira et al [22] (2021).…”
Section: Discussionmentioning
confidence: 98%
“…With an understanding that this was a convenience sample, it was not possible to address any trends that may have increased or reduced the impacts of these lawsuits on the state's health management, although it was possible to describe the characteristics and behavior of expenditure on medications and the relevance of antineoplastic drugs in a Northeastern Brazilian state that ranks as one of the richest (GDP) in the region. The following comparisons with other ndings in the literature have limitations, since the studies present different methodologies for collecting and describing the pro le characteristics of judicialization, as recently cited by Oliveira et al [22] (2021).…”
Section: Discussionmentioning
confidence: 98%
“…It was possible, however, to describe the characteristics and trends relating to expense on medication and the proportion of this associated with antineoplastic drugs in a Northeastern Brazilian state that is one of the wealthiest (in terms of GDP) in the region. Attention should be drawn to a few shortcomings regarding the following comparison of our findings with those of other studies in the literature, in view of the variety of methodologies that have been used to collect and describe the characteristics of lawsuits, as recently noted by Oliveira et al (2021) [21]. Our description of the profile of litigation relating to healthcare in the State of Pernambuco found that the proportion of lawsuits was similar for both sexes, thereby corroborating the findings of Diniz et al [22], who found that 51% of such lawsuits in the Federal District (DF) were filed by men.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible, however, to describe the characteristics and trends relating to expense on medication and the proportion of this associated with antineoplastic drugs in a Northeastern Brazilian state that is one of the wealthiest (in terms of GDP) in the region. Attention should be drawn to a few shortcomings regarding the following comparison of our findings with those of other studies in the literature, in view of the variety of methodologies that have been used to collect and describe the characteristics of lawsuits, as recently noted by Oliveira et al (2021) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear how much these legal demands put pressure on the adoption of drugs by the CONITEC. In Rio Grande do Norte, four of the ten most demanded drugs between 2013 and 2017 were later adopted by the CONITEC (25), suggesting an association between the demands and the adoption. Souza et al (26), on the other hand, found no direct relationship between lawsuits for biological drugs and their adoption by the CONITEC.…”
Section: Discussionmentioning
confidence: 99%